«Methodologies of forming constituents of vocational competence of future power grid automation engineers - Lazarev, N; Rudevich, N. (Problems of Engineer-Pedagogical Education, 2019)
The article presents methodologies of forming project, operating, research, economic, socioadministrative and legal competences of future power grid automation engineers on the basis of the worked out causal content and methods of the causal development of vocational competence constituents, whose basis is the establishment of causal connections and chains of knowledge. Methodologies of forming project and operating competences reflect the solution of professional tasks while carrying out design works and technical verification of the systems of managing the objects of power grids. Professional tasks related to conducting scientific research and technical-economic substantiation of the systems of managing power grids objects form the basis of methodologies aimed at developing research and economic competences. Methodology aimed at developing legal competence represents the professional decision making in accordance with the requirements of normative documents, whereas methodology aimed at developing socially-administrative competence represents administrative decision making concerning project, operating and research activities of future power grid automation engineers.